Cerebellar Metastasis From Ovarian Carcinoma Harboring PIK3CA-Activating Mutation: A "Clear" Explanation for Unexpected "Vertigo". (January 2020) - Piermattei, Alessia; Santoro, Angela; Angelico, Giuseppe; Inzani, Frediano; Valente, Michele; Pettinato, Angela; Vatrano, Simona; Scambia, Giovanni; Fraggetta, Filippo; Zannoni, Gian Franco
Abstract : Brain metastasis is a rare and generally late manifestation of an advanced-stage, high-grade serous ovarian carcinoma. Nowadays, the improved control of intra-abdominal disease by surgery and platinum-based chemotherapy results in a longer survival, allowing distant metastasis to implant and grow in the brain parenchyma. Herein, we describe a unique case of a cerebellar metastasis from clear cell ovarian carcinoma that initially presented as a FIGO Stage IC cancer. Surprisingly, 6 mo after surgery, the patient was in good condition with complete disappearance of symptoms and no evidence of recurrence. This relatively good biologic behavior may be explained by the presence of a PIK3CA -activating mutation in exon 9 which as previously reported in the literature, may be associated with better prognosis. To the best of our knowledge, this is the first reported case of cerebellar metastasis from ovarian clear cell carcinoma. In the presence of neurological symptoms, both clinicians and pathologists must be aware of this rare possibility, to assure correct patient management and effective therapeutic options. Generally, the prognosis of epithelial ovarian cancer patients with brain metastases is poor. PIK3CA mutations could be a good prognostic indicator in clear cell carcinomas.